Petani Muslim Kuningan Dalam Pusaran Konflik Kelas - Nanang Hasan Susanto (Jurnal Penelitian, 2016)
This study examines Marx's theory which says that in the process of capitalization, small land farmers will be displaced by large land farmers. This study uses a qualitative approach with the method of Participatory Action Research (PAR). Using the techniques of participatory observation in the field, the study conducted in-depth interviews on farmers. Analysis of the data used is inductive. This study led to the conclusion that Marx's theory does not happen in Aman malar. The cause of the decline of agriculture due to declining soil nutrients, the high cost of production, land use and climate change. While the strategies of small land farmers to sustain life is to do the planting patterns of intercropping, do extra work, and manage finances.